Unlocking Ugandan pumpkin landrace diversity: integratedmorphological and nutritional profiling for food security andbreeding innovation - Fred Bwayo Masika; Godwin Anywar; Mahipal Singh Kesawat; Gabriel Ddamulira; Caro Kawuma; Morgan Andama; Charity Ajoma; Idd Ramathan; Otuba Moses Amugoli; Jimmy Caku; Titus Alicai; Ephraim Nuwamanya; et al. (Taylor & Francis Group, 2026)
Pumpkins (Cucurbita spp.) are vital for food and nutritional security in Uganda, yet their full potential remains underexploited due to the limited characterization of traits. To address this, 91 landraces, 21 Cucurbita pepo and 70 Cucurbita moschata were collected from 19 districts across major agroecological zones, evaluated for morpholological and nutritional diversity. Results revealed wide phenotypic variation with fruit weights ranging from 0.5 to 10.0 kg and shapes varying from discoid (L/D 0.44) to highly elongated (L/D 4.00). Fruit size and shape were independent axes of variation. Regionally, Buganda and Bunyoro landraces produced larger fruits, averaging 3.84 kg and 4.07 kg, while West Nile landraces formed a distinct nutrient-rich cluster, with high dry matter (22.8%), lipids (3.75% fresh weight (FW), fiber (3.34% FW), and carbohydrates (4.07% FW). District-specific differences were also observed, with Mpigi landraces rich in phenolics content (0.062 ± 0.0023 g GAE/100 g), and Mukono landraces rich in proteins (0.000887 g/100 g). Importantly, external morphology poorly predicted internal nutritional quality, highlighting the need for direct biochemical profiling in breeding programs. This study provides Uganda’s first nationally structured dataset on pumpkin diversity, offering a scientific foundation for targeted germplasm conservation, nutrient-enriched cultivar development and policy interventions to strengthen food systems across diverse agroecological zones in Uganda.
Keywords: Cucurbita spp.; morphologicalcharacterization; nutritional composition; geographical variation; germplasm conservation; diversity; food security